The Study of the Narrative Identity of Russian and Chinese Students - Suvorova, I.Y.; Glebov, V.V.; Wang, H. (Socialʹnaâ Psihologiâ i Obŝestvo, 2021)
Objective. The article is devoted to the analysis of the narrative identity of Chinese and Russian students. It was assumed that the reflection of the socio-political situation is more obvious and manifests itself in the main themes and attitudes, reflecting both the content side of the narrative and its structure, while the identification of cultural influence requires additional analysis. Background. Cross-cultural studies point to the need to analyze the narrative at the individual, political, social, economic and cultural level. In theory, each of the levels has its own influence on the structure and content of the narrative. Nevertheless, there is an extremely small amount of practical data on the comparison of various types of analysis and the peculiarities of their manifestation in narrative. Study design. The article analyzed the features in the presentation of fragments of biography, the manner of presenting information and mentioning the main topics of the citizens of countries with a different socio-political system. Participants. The sample consisted of 80 people: 35 narratives of students from the PRC (19 male and 16 females from 19 to 26 years old) and 45 narratives of students from the Russian Federation (PFUR) (17 male and 28 females from 20 to 23 years old). All participants were born between 1997 and 2000. Measurements. The article used the analysis of narrative identity of K. McLean and D. McAdams both as a theory and as research method. Statistical analysis included the calculation of differences between the two samples (Mann-Whitney U test) and hierarchical cluster analysis. Results. The narratives of Russian and Chinese students reflect inconsistency and a high degree of uncertainty of the socio-political situation in Russia, as well as great social pressure and high competition in China. Conclusions. The structure of narrative identity primarily reflects the socio-political situation as related to the direct experience of students. Cultural experience affects more fundamental personality constructs and is not read in ordinary narrative analysis. Цель. Статья посвящена анализу нарративной идентичности китайских и российских студентов. Предполагалось, что отражение социально-политической ситуации более очевидно и проявляет себя в основных темах и установках, отражающих как содержательную сторону нарратива, так и его структуру, тогда как выявление культурного влияния требует дополнительного анализа. Контекст и актуальность. Кросс-культурные исследования указывают на необходимость анализа нарратива на индивидуальном, политическом, социальном, экономическом и культурном уровнях. Теоретически каждый из уровней имеет свое влияние на структуру и содержание нарратива. Тем не менее существует сравнительно небольшое количество данных о сопоставлении различных видов анализа и особенностей их проявления в нарративе. Дизайн исследования. В работе анализировались различия в изложении фрагментов биографии, в манере преподнесения информации и в упоминании основных тем жителями стран с различным социально-политическим строем. Участники. Выборку составили 80 человек: 35 нарративов студентов из КНР (19 мужчин и 16 женщин в возрасте от 19 до 26 лет) и 45 нарративов студентов из Российской Федерации (РУДН) (17 мужчин и 28 женщин в возрасте от 20 до 23 лет). Все участники исследования родились в период с 1997 по 2000 годы. Методы (инструменты). В статье применялся нарративный анализ идентичности К. Маклин и Д. МакАдамса как теория и метод исследования. Статистический анализ включил вычисление различий между двумя выборками (критерий U Манна-Уитни) и иерархический кластерный анализ. Результаты. Полученные результаты показывают, что в нарративах российских и китайских студентов отражены непоследовательность и большая степень неопределенности социально-политической ситуации в России, а также большое социальное давление и высокая конкуренция в Китае. Основные выводы. В структуре нарративной идентичности в первую очередь отражается социально-политическая ситуация как связанная с непосредственным опытом студентов. Культурный опыт затрагивает более фундаментальные конструкты личности и в обычном нарративном анализе не считывается.